Need Analysis of training courses related to GNSS interference in critical national infrastructure applications for GRACE - Khandelwal, Ayush (2012)
It is clearly evident that global positioning system, more commonly known as GPS has become a part and parcel of our daily lives. This is because of the easy and cheap availability of GPS and other global navigation satellite systems (GNSS). The use of this technology can be found in surveying, maritime navigation, in-car navigation and numerous other applications. One needs to be reminded that each of the segments of any global navigation satellite systems are prone to failures of various types and these failures can result into a variety of consequences and impact both the users and producers of the technology in various ways. Solutions and mitigation strategies to the various failure modes of GNSS signals are available but there is still a long way to go in terms of having a fool-proof system application in place. This gap can be filled by awareness and training programmes in terms of assessing the failures modes and developing the best possible responses and strategies. This report looks into this issue of GNSS signal vulnerabilities and looks at the need for awareness and training programmes that the organization conducting the research can look into. The report performs a qualitative need analysis for awareness and training programmes related to GNSS failures, impacts and possible solutions. A number of ideas have been generated here in context to the (a) the awareness of GNSS issues, (b) the capabilities of GRACE and value co-creation and value flow, (b) target market and target audience and (d) the structure of a course of this nature. The research takes a qualitative perspective with inputs and suggestions from industry experts and attempts to provide a new thought process to GRACE as an organization.